Evaluation and memory of social events in borderline personality disorder: effects of valence and self-referential context - Winter, Dorina; Schmahl, Christian; Bohus, Martin (Psychiatry research, 2016)
People's memory of past social encounters influences current social interactions. Social rejection has been shown to increase people's memory for social events particularly when referring to others rather than themselves. Social rejection and neglect often characterize biographies of individuals with borderline personality disorder (BPD). Using a social memory task, we investigated whether the evaluation and memory of social events is altered in BPD and whether this depends on reference to the self or others. 30 patients with BPD and 30 healthy controls evaluated the valence of positive, neutral, and negative standardized events, which were either social or nonsocial. Subsequently, participants had to recall these events. BPD patients evaluated social events of negative and neutral valence as more negative than healthy controls. Further, only BPD patients tended to preferentially recall self-referential social events. These findings suggest altered self-referential processing of social events that affects both the evaluation and the memory for social events.